Prognostic Value Of Fetal Urinary Beta-2 Microglobuline In Vesicoamniotic Shunting Therapy For Fetal Obstructive Uropathy - Gil-Guevara, Enrique Damián (2017)
Introduction and objectives. Fetal obstructive uropathy can be treated early in pregnancy by intrauterine vesicoamnioticshunting, immediately after being diagnosed by ultrasound, in specific cases with a favorable prognosis in renal function usingfetal urinary beta-2 microglobuline. The main objective of the study was to determine the changes of beta-2 microglobulinein consecutive samples of fetal urine in 48 – 72 hour-intervals in fetuses with obstructive uropathy at 16 weeks of gestation.Methods. We performed a descriptive and longitudinal study, including 15 pregnant women whose fetuses were diagnosedwith obstructive uropathy and without chromosomal abnormalities, performing vesicocentesis for urinary biometry.